2014
DOI: 10.1542/peds.2014-1024
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Nonviral Sexually Transmitted Infections in Adolescents and Young Adults

Abstract: Prevalence rates of many sexually transmitted infections (STIs) are highest among adolescents. If nonviral STIs are detected early, they can be treated, transmission to others can be eliminated, and sequelae can be averted. The US Preventive Services Task Force and the Centers for Disease Control and Prevention have published chlamydia, gonorrhea, and syphilis screening guidelines that recommend screening those at risk on the basis of epidemiologic and clinical outcomes data. This policy statement specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…This is concerning because current recommendations for STI screening by the CDC, USPSTF, and AAP recommend annual screening. (4–6) If these patients were screened only annually, the patients found to be positive in our study may have gone undetected for several months, increasing the risk of both infection-related morbidity and further spread of infection to others. Additionally, almost one-third of those infected had never previously undergone STI screening, further supporting ED-based STI screening programs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is concerning because current recommendations for STI screening by the CDC, USPSTF, and AAP recommend annual screening. (4–6) If these patients were screened only annually, the patients found to be positive in our study may have gone undetected for several months, increasing the risk of both infection-related morbidity and further spread of infection to others. Additionally, almost one-third of those infected had never previously undergone STI screening, further supporting ED-based STI screening programs.…”
Section: Discussionmentioning
confidence: 96%
“…(2) For these reasons, the Healthy People 2020 objectives identify as a national priority addressing the STI epidemic with a specific focus on STI reduction in adolescents. (3) The American Academy of Pediatrics(4) (AAP), Centers for Disease Control and Prevention(2) (CDC), and the US Preventative Services Task Force(5) (USPTF) all recommend at least annual STI screening among sexually active females. The AAP(4) and CDC(2) also recommend at least annual STI screening for sexually active males in settings with high prevalence rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While all are acceptable, the Centers for Disease Control and Prevention (CDC) states vaginal swabs are the optimal standard and urine samples may have slightly reduced performance. 3 , 4 Cervical examinations are no longer routinely recommended for adolescents. 5 Studies have demonstrated adolescent females prefer less invasive methods (urine and self-collected vaginal swabs) compared to invasive cervical swabs that require a speculum exam.…”
Section: Introductionmentioning
confidence: 99%
“…These goals require particular focus on adolescents [6]. In the US, adolescents and young adults (15–24 years) account for nearly two-thirds of new chlamydia infections and 70% of new gonorrhea infections [7,8].…”
Section: Introductionmentioning
confidence: 99%